(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2021)
One of the most original, recent contributions of contemporary European seriality to the crime genre has been the introduction of a notable number of detectives repeatedly diagnosed as autistic by autistic online communities. Titles such as the Millennium saga, Sherlock, Forbrydelsen, Bron/Broen, and, more recently, Astrid et Raphaëlle, are all widely debated within autistic online communities. This article investigates the unique critical perspective brought by the autistic parlance on these popular products, through a survey of blogs, social networks, fanfiction, and videos, in English and French. The analysis of this material reveals that there is a whole spectrum of different opinions among autists when it comes to their approval, or disapproval, of media representations of neurodiversity, oscillating between complaints for the persistence of the ‘savant autist’ stereotype and a grateful appreciation of the effort to portray the condition in positive and empowering ways. Most of the comments reflect the stances of the neurodiversity movement and the complex context of autism advocacy, by which autistic individuals reclaim the right to speak for themselves and stand up to fight for a more inclusive society.